2015
DOI: 10.1159/000373976
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Regulates Hepatocellular Carcinoma Progression by Inducing Treg Cell Polarization

Abstract: Background/Aims: TGF-β plays a key role in the progression of various tumors. The main objective of our study was to investigate whether TGF-β is able to regulate N-nitrosodiethylamine (DEN)-induced hepatocellular carcinoma (HCC) progression in a mouse model by inducing Treg cell polarization. Methods: HCC progression, TGF-β and Foxp3 expression levels, serum TGF-β, IL10 and GP73 levels as well as percentage of Treg cells were analyzed in healthy, HCC and HCC+SM-16 mouse groups. The effect of TGF-β on Treg cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 34 publications
3
81
0
2
Order By: Relevance
“…TGF-β inhibits many biological processes, including T cell proliferation, the differentiation of T cells into cytotoxic T lymphocytes, and helper T-cells and T-cell stimulatory functions of antigen-presenting cells [33, 34]. TGF-β has also been found to promote the differentiation of regulatory T cells in vitro [35]. Hence, among the roles that have been identified for ZMIZ1, its role in modulating TGF-β is exciting for IBD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β inhibits many biological processes, including T cell proliferation, the differentiation of T cells into cytotoxic T lymphocytes, and helper T-cells and T-cell stimulatory functions of antigen-presenting cells [33, 34]. TGF-β has also been found to promote the differentiation of regulatory T cells in vitro [35]. Hence, among the roles that have been identified for ZMIZ1, its role in modulating TGF-β is exciting for IBD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that TGFβ expression in tumor cells is promoted by surrounding cells in the tumor microenvironment [28]. It has been reported that TGF-β1 was overexpressed in several cancers such as hepatocellular carcinoma and it was related to the progression of tumor cells [29, 30]. AP-1 helps to regulate host immune responses and is up-regulated in many types of cancer, including breast cancer and pancreatic cancer [31-33].…”
Section: Discussionmentioning
confidence: 99%
“…They also harbor a receptor protein, cytotoxic T-lymphocyteassociated protein 4 (CTLA-4), latently expressing TGF-β on the membrane surface [11]. Although a large number of signaling pathways participate in the regulation of Treg cells [12][13][14][15], forkhead box protein 3 (Foxp3) as Treg specific transcription factor is the most important one. Diminished expression of Foxp3 in CD4 + CD25 + Treg cells created dysfunction of Treg cells in SLE [16].…”
Section: Introductionmentioning
confidence: 99%